A Perspective on Organizational Change Issue – Case Study on the Application of Two Change Models - Oliviana BOLD (Revista de Management Comparat International)
The organization is a social system in which people interact to achieve common goals. We observe an acceleration of change in the value systems worldwide, an adoption of new attitudes, new goals, and aspects leading to rapid change of the society. To survive and develop, an organization must first know how to anticipate and capitalize on the opportunities and to attenuate or eliminate the vulnerabilities. Second, the organization must demonstrate the ability to effectively manage the change process, from detailed investigation of its past and present. These are the fundamental premises on which the change management is based. The research and practice of the change management models summarize a basis for understanding the change processes and mechanisms at both organizational and individual levels. In the following we will present some change management models that may be useful in managing change in economic organizations and whose applicability and implementation proved to be effective for identifying outcomes of change in organizations.